A Review of Frequency Selection and Antenna Arrangement System for Microwave Imaging in Early Breast Cancer Detection - Hadi, Jumaat; Mohd Tarmizi, Ali; Kismet, Hong Ping; Najwa, Mohd Faudzi; Nurfarahin, Miswadi; Hamizan, Yon (IOP Publishing Ltd, 2019)
Microwave imaging technique is one of the developing techniques that having attention by researcher around the world in early breast cancer monitoring due it is non-ionizing and the potential for cost saving and simpler system as compared to the current imaging techniques. The frequency selection is crucial in this application due to no bandwidth proven best. However, the amount of antenna is said affected the image resolution. This paper is an attempt to review the frequency selection and the antenna arrangement system in the past decades works for future antenna development in early breast cancer detection.